Composition measurement of epitaxial ScxGa1−xN films. (19th May 2016) - Tsui, H C L; Goff, L E; Barradas, N P; Alves, E; Pereira, S; Palgrave, R G; Davies, R J; Beere, H E; Farrer, I; Ritchie, D A; Moram, M A
Abstract: Four different methods for measuring the compositions of epitaxial Sc x Ga1− x N films were assessed and compared to determine which was the most reliable and accurate. The compositions of epitaxial Sc x Ga1− x N films with 0 ≤  x  ≤ 0.26 were measured directly using Rutherford backscattering (RBS) and x-ray photoelectron spectroscopy (XPS), and indirectly using c lattice parameter measurements from x-ray diffraction and c / a ratio measurements from electron diffraction patterns. RBS measurements were taken as a standard reference. XPS was found to underestimate the Sc content, whereas c lattice parameter and c / a ratio were not reliable for composition determination due to the unknown degree of strain relaxation in the film. However, the Sc flux used during growth was found to relate linearly with x and could be used to estimate the Sc content.